Metabolic transition from childhood to adulthood based on two decades of biochemical time series in three longitudinal cohorts - Mäkinen, Ville-Petteri; Kähönen, Mika; Lehtimäki, Terho; Hutri, Nina; Rönnemaa, Tapani; Viikari, Jorma; Pahkala, Katja; Rovio, Suvi; Niinikoski, Harri; Mykkänen, Juha; Raitakari, Olli; Ala-Korpela, Mika (Oxford University Press, 2026)
Background: This is the first large-scale longitudinal study of children that describes the temporal trajectories of an extensive collection of metabolic measures that are relevant for lifelong cardiometabolic risk. We also provide a comprehensive picture on how metabolism develops into mature adult sex-specific phenotypes.
Methods: Children born in 1962-92 were recruited by three European studies (n = 20 377 eligible). Biochemical data for ages 0-26 years were available for n = 14 958 participants (n = 8385 with metabolomics). Age associations for 168 metabolic measures (6 physiological traits, 6 clinical biomarkers, and 156 serum metabolomics measures) were determined by using curvilinear regression. Puberty effects were calculated by using logistic regression of biological sex for pre- and post-pubertal age strata.
Results: Age-specific concentrations were reported for all measures. Nonlinear age associations were typical, including insulin (R2 = 20.7% ±0.6% variance explained ±SE), glycerol (13.3% ±1.3%), glycoprotein acetyls (40.3% ±1.5%), and branched-chain amino acids (19.5% ±1.6%). Apolipoprotein B was not associated with age (0.7% ±0.4%). Multivariate modeling indicated that boys diverged from girls metabolically during ages 13-17 years. Puberty effects were observed for large high-density lipoprotein cholesterol (P = 8.5 × 10-288), leucine (P < 2.3 × 10-308), glutamine (P < 2.3 × 10-308), albumin (P = 1.7 × 10-161), docosahexaenoic acid (P = 5.2 × 10-50), and sphingomyelin (P = 4.4 × 10-90).
Conclusion: Novel associations between emerging cardiometabolic risk factors, such as amino acids and glycoprotein acetyls, and growth and puberty were observed. Conversely, apolipoprotein B was stable, which favors its utility for early assessments of lifetime cardiovascular risk.
Keywords: amino acids; apolipoprotein B; cardiovascular risk factor; children; inflammation; insulin; lipids; longitudinal; metabolism; puberty.